Developmental Disabilities in Children Involved with Child Welfare: Correlates of Referrals for Service Provision. Issue 2 (14th March 2016) - Simmel, Cassandra; Merritt, Darcey; Kim, Soyoun; Kim, Hillary Mi-Sung
Abstract : Using data from the National Survey of Child and Adolescent Well-being (NSCAW), this study explores the characteristics of child welfare involvement for children ( N  = 639; aged 3–17.5 years) with at least one developmental disability. In addition, a central focus of this exploration was to examine respective differences in how caregivers and caseworkers initiated referrals for services for children with disabilities. The sample was divided into three exclusive groups based on type of developmental disability: learning disability (weighted percentage 70.3%); Mental Retardation (now referred to as Intellectual Disability), Downs Syndrome, or; developmental delay (weighted percentage 1.8%); and presence of multiple types of disabilities, including autism (weighted percentage 27.9%). Results from the logistic regression analyses indicate children in this population who are placed in out-of-home care receive more referrals than those residing in-home with biological caregivers; older children and children with multiple disabilities are also more apt to obtain referrals to formal assessments. On the other hand, children who were considered in the "other" race category (includes children who identify as: multi-racial; Asian; Pacific Islander; Native American) were significantly less likely to be referred for a formal assessment. Regarding the association between specific maltreatment type and assessment referrals, children with reports of emotional maltreatment had significantly higher odds of being referred for formal assessments.